Jet Stream Injury From Triamcinolone Acetonide Leading To Perifoveal Tear - Manabjyoti Barman; Minakshi Sheokand; Pushkar Dhir (Delhi Journal of Ophthalmology)
Managing iatrogenic hole in peri-foveal area in the most unexpected mannerwhile planning for macular hole surgery has been a daunting task for the surgeon leaving a big dilemma to peel or not to peel, to go ahead with endo-laser or tamponade or just to abandon the surgery. We report a case of 68 year old female who encountered spontaneous closure of iatrogenic peri-foveal hole formed by triamcinolone crystal plug hitting the peri-foveal area just before ILM staining.